The Signaling Effect of Durations between Equity and Debt Issues. Issue 2 (May 2015) - Bilinski, Pawel; Mohamed, Abdulkadir
Abstract : This study examines whether durations between equity and debt offerings allow investors to identify firms that are more likely to time issues of overvalued securities. We show that firms with higher stock overpricing are more likely to quickly issue both seasoned equity and debt following the previous capital acquisition. Investors understand issuers' incentives to quickly return to the capital market and react less favorably to equity and debt issues that follow shortly after the previous offering. Together, the results show that durations between equity and debt issues provide valuable signals to investors on whether the issuer is likely to be timing the market.